Doxycycline reduces fibril formation in a transgenic mouse model of AL amyloidosis - Ward, Jennifer Ellis (American Society of Hematology, 2011)
Systemic AL amyloidosis results from the aggregation of an amyloidogenic immunoglobulin (Ig) light chain (LC) usually produced by a plasma cell clone in the bone marrow. AL is the most rapidly fatal of the systemic amyloidoses, as amyloid fibrils can rapidly accumulate in tissues including the heart, kidneys, autonomic or peripheral nervous systems, gastrointestinal tract, and liver. Chemotherapy is used to eradicate the cellular source of the amyloidogenic precursor. Currently, there are no therapies that target the process of LC aggregation, fibril formation, or organ damage. We developed transgenic mice expressing an amyloidogenic λ6 LC using the cytomegalovirus (CMV) promoter to circumvent the disruption of B cell development by premature expression of recombined LC. The CMV-λ6 transgenic mice develop neurologic dysfunction and Congophilic amyloid deposits in the stomach. Amyloid deposition was inhibited in vivo by the antibiotic doxycycline. In vitro studies demonstrated that doxycycline directly disrupted the formation of recombinant LC fibrils. Furthermore, treatment of ex vivo LC amyloid fibrils with doxycycline reduced the number of intact fibrils and led to the formation of large disordered aggregates. The CMV-λ6 transgenic model replicates the process of AL amyloidosis and is useful for testing the antifibril potential of orally available agents.